2001
DOI: 10.1096/fj.00-0459fje
|View full text |Cite
|
Sign up to set email alerts
|

Molecular andin silicocharacterization of a promoter module and C/EBP element that mediate LPS‐induced RANTES/CCL5 expression in monocytic cells

Abstract: The chemokine RANTES/CCL5 is a proinflammatory agent produced by a variety of tissues in response to specific stimuli. In human monocytes, RANTES/CCL5 transcription is up-regulated rapidly and transiently in response to LPS. We describe here two regions that help control LPS-driven transcription from the human RANTES/CCL5 promoter in monocytic cells. These sites were analyzed by using DNase I footprinting, transient transfection assays, site-directed mutagenesis, and EMSA. RANTES site E (R(E), -125/-99) consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 60 publications
2
42
0
Order By: Relevance
“…Many different monocytic cell lines, including THP-1 cells, show constitutive nuclear B activity (31), and unlike MIP-1␣, RANTES has two B sites near the TATA signal, thus explaining possible interactions with components of the general transcription machinery that could account for the expression of RANTES detected in resting cells. In contrast, the delayed pattern of RANTES mRNA induction by IC agrees with the characterization of RANTES as an unusual gene induced late after T lymphocyte activation, the expression of which has been related to a novel transcription factor termed RANTES factor of late activated T lymphocytes, which belongs to the Kruppel-like family of transcription factors (32), although other factors have been associated with the cell-specific pattern of transcriptional regulation of RANTES, among them NF-B (33), C/EBP␤ (34), and IFN regulatory factor (35).…”
Section: Discussionsupporting
confidence: 77%
“…Many different monocytic cell lines, including THP-1 cells, show constitutive nuclear B activity (31), and unlike MIP-1␣, RANTES has two B sites near the TATA signal, thus explaining possible interactions with components of the general transcription machinery that could account for the expression of RANTES detected in resting cells. In contrast, the delayed pattern of RANTES mRNA induction by IC agrees with the characterization of RANTES as an unusual gene induced late after T lymphocyte activation, the expression of which has been related to a novel transcription factor termed RANTES factor of late activated T lymphocytes, which belongs to the Kruppel-like family of transcription factors (32), although other factors have been associated with the cell-specific pattern of transcriptional regulation of RANTES, among them NF-B (33), C/EBP␤ (34), and IFN regulatory factor (35).…”
Section: Discussionsupporting
confidence: 77%
“…Because mutations at the C/EBP binding site exhibited a more significant inhibition of LPS response than did mutations at Sp1 binding site, the C/EBP binding site seems to play a more important role in the LPS response. According to related literature, it is known that C/EBP is important for some gene expressions, e.g., endotoxin-induced cyclooxygenase-2 gene (24), IL-1␤-induced IL-6 gene (25), and LPS-induced IL-1␤ gene (26) and RANTES/chemokine (C-C motif) ligand 5 gene (27). Recently it was reported that C/EBP␣ and ␤ are critical in both basal and cAMP/stress-dependent induction of human IL-10 expression during monocytic differentiation (28).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear extracts were prepared 26 h later as described in ref. 22. Samples of the nuclear extract or the cytoplasmic fraction were run on SDS͞PAGE under reducing conditions and electrophoretically transferred onto poly(vinylidene difluoride) membranes.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were harvested 26 h after transfection, and nuclear extracts were prepared as described in ref. 22. Five micrograms of protein of each extract was analyzed by Western blot.…”
Section: Traf2 Traf5 and Nik Contribute To Cd40-mediated Activationmentioning
confidence: 99%